Factores de riesgo neonatales asociados a prolongación de estancia promedio por GDR en Neonatología del HRDT 2011-2014 - Medina Huayta y Colls., Mareyke Natividad (2018)
The hospital stay is a good indicator of the quality of health care among the factors that have affected the severity of the disease, psychosocial and institutional. The optimum stay depends on the characteristics of the patient. The stay average (SA) for Diagnosis Related Groups (DRG) allocating resources in proportion to the complexity of diagnosis and treatment, very important for areas such as neonatology where patients spend prolonged periods in intensive and intermediate care. The study objective was to assess whether risk factors: Apgar at 5 minutes less than 6, perinatal asphyxia, neonatal resuscitation and admission to any type Intensive Care Unit (ICU), are associated with prolongation of the SA in hospitalized patients in the Neonatology Service of Regional Hospital of Trujillo (HRDT) during the period 2011 - 2014. Population and Methods. A study of cases and controls matched in Neonatology HRDT during the period 2011 – 2014. Patients remained hospitalized for social neglect were excluded. Of a population of 3233 patients, a sample of 447 cases and 1341 controls by EPIDAT. The sample proportionally distributed by groups stratified according to the GDR: Group 1 (<750 g), Group 2 (750-1000 g), Group 3 (1000-1500 g), Group 4 (1500-2000 g), Group 5 (2000-2500 g) and Group 6 (> 2500 g). The source of information was the database HRDT Neonatology. For statistical analysis, a logistic regression model was used. Results. The minimum stay was 0 days (deceased on the day of admission) and the maximum 133 days. When performing stratification by weight groups, the average stay for each group was obtained, as SA for groups 2 and 3 (27 and 28 days), the group 1 where patients are located less weight had an SA 16.47 which is related to early mortality. Less SA groups are 5 and 6 (greater than 2000 grams). By logistic regression model used was determined that the risk factors studied, only admission to ICU has significant association with the extension of the average stay. Conclusion. Admission to the neonatal intensive care unit is the most important determinant of hospital stay in the different groups assessed to distribute to patients for diagnosis related groups. The results of our study contrast with those reported in the literature because the designs employed do not allow stratification of the average stay per GDR, so it is recommended to develop new designs considering this distribution, especially for neonatology where patients have particular characteristics dependent of their birth weight.